Tarjamah Tafsiriah Terhadap Al-Qur’an: Antara Kontekstualisasi dan Distorsi - Syahrullah Syahrullah (JOURNAL OF QUR'AN AND HADITH STUDIES, 2013)
The Qur’an translation in Bahasa Indonesia by the Ministry of Religious Affairs has been criticized by Majelis Mujahidin Indonesia. This translation, according to them, is one of the factors that produces radicalism. On the basis of this claim, this article discusses Tarjamah Tafsiriyah: Memahami Makna al-Qur’an Lebih Mudah dan Cepat (2011) by Muhammad Thalib, the Amir of MMI. Using the descriptive analysis approach, this article shows that Tarjamah Tafsiriyah has several advantages, such as its short redaction and interpretive translation, although worth criticizing the emphasis on a certain meaning and the lack of attention to the text’s variety of meaning.